Marketing and distribution strategies of ACI Logistics Limited (SHWAPNO- lifestyle department) - Akib, Faisal Karim (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.